Unlocking the potential of wild edibles - Borelli, Teresa; Hunter, D. (International Union for Conservation of Nature, 2013)
Many wild edible species are disappearing due to environmental pressures or to neglect as populations worldwide move away from traditional food systems towards more simplified and energy-rich diets and become averse to consuming traditional dishes that are perceived as “food for the poor”, only to be drawn upon in times of food scarcity.